2023
DOI: 10.3390/polym15204048
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Recognition Property of Tyrosine Molecularly Imprinted Polymer Prepared via Electron Beam Irradiation

Pengpai Miao,
Yanan Sang,
Jie Gao
et al.

Abstract: To realize the selective separation of L-tyrosine (L-Tyr) and avoid the drawbacks of traditional thermal polymerization, electron beam irradiation polymerization was developed for the fabrication of L-Tyr molecularly imprinted polymers (MIPs). Firstly, L-Tyr MIPs were prepared with methacrylic acid and ethylene glycol dimethacrylate and without an initiator. Then, the influence of absorbed dosage and temperature on the adsorption capacity of L-Tyr, as well as the thermodynamic behavior, were investigated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…In addition, the ∆H 0 and ∆S 0 were −2.21 kJ/mol and −5.8 J/mol•K, respectively. The negative value of ∆H 0 shows that LOF adsorption is exothermic, in agreement with other data, and the positive value of ∆S 0 shows that GO/CS aerogel microspheres have good affinity for LOF [26,37].…”
Section: Effect Of Temperature and Thermodynamicssupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, the ∆H 0 and ∆S 0 were −2.21 kJ/mol and −5.8 J/mol•K, respectively. The negative value of ∆H 0 shows that LOF adsorption is exothermic, in agreement with other data, and the positive value of ∆S 0 shows that GO/CS aerogel microspheres have good affinity for LOF [26,37].…”
Section: Effect Of Temperature and Thermodynamicssupporting
confidence: 91%
“…As shown in Table 1, with the increase in temperature, the ∆G 0 increased from −0.51 to −0.33 kJ/mol, revealing that the adsorption process is spontaneous. This result also indicated that low temperatures are beneficial for the adsorption of LOF, a finding that is consistent with the results for the effect of temperature on adsorption [37,38]. In addition, the ∆H 0 and ∆S 0 were −2.21 kJ/mol and −5.8 J/mol•K, respectively.…”
Section: Effect Of Temperature and Thermodynamicssupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, Figure 4 c displays that the system is very close to the equilibrium within 5 min. Therefore, according to the study by Simonin, caution should be exercised when comparing PFO kinetics with PSO kinetics [ 55 ]. Because for the PFO model, when q t approaches q e , the value of (q e – q t ) becomes smaller and smaller, leading to the accuracy reduction of k1.…”
Section: Resultsmentioning
confidence: 99%